The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.3727/154427205774791744
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Training and Measures at Scandic Hotels, Sweden

Abstract: Mass tourism destinations and facilities, accounting for the most significant share of the global tourism market, are still largely managed with little or no environmental concern. The willingness and ability of facility management and staff to adopt greater environmental awareness and responsibility is crucial in striving towards a higher degree of sustainability in the tourism sector. The aim of this article is to provide an overview of the environmental proactiveness and ground-breaking work that has been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 10 publications
0
51
0
2
Order By: Relevance
“…They are also aware that the hotel industry would benefit from environmental pro-activeness among operators. In response to emerging customer demand for ''green'' operations, combined with the growing evidence of financial benefits from managing resource-efficient facilities (UNEP and IH&RA, 1997;Martinac, et al, 2001;SSCC, 2003;Bohdanowicz, et al, 2005), hoteliers are more willing to make changes to accommodate pro-ecological programmes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also aware that the hotel industry would benefit from environmental pro-activeness among operators. In response to emerging customer demand for ''green'' operations, combined with the growing evidence of financial benefits from managing resource-efficient facilities (UNEP and IH&RA, 1997;Martinac, et al, 2001;SSCC, 2003;Bohdanowicz, et al, 2005), hoteliers are more willing to make changes to accommodate pro-ecological programmes.…”
Section: Discussionmentioning
confidence: 99%
“…Increasingly stringent environment-related regulations are now being adopted and enforced in many parts of the world, including the EU. Hotel and tourism organisations and even hotel companies are developing environmental guidelines, training programmes and publishing best practice case studies (IHEI, 1993;IH&RA et al, 1995;UNEP and IH&RA, 1997;Accor Group, 1998;SHR, 1999;Genot et al, 2001;Bergkvist, 2004;Bohdanowicz et al, 2005). Pro-ecological initiatives are becoming increasingly popular among hoteliers worldwide.…”
Section: Hotels and The Environmentmentioning
confidence: 99%
“…Weeden (2002) suggested that this can be achieved by ensuring that practices are transparent and can be viewed by all stakeholders, shareholders, employees and communities (Wheeler, 1990(Wheeler, , 1991. Significant research has emerged about CSR behaviour and ethics among tourism and hospitality enterprises (see Ayuso, 2006Ayuso, , 2007Bohdanowicz, Simanic, & Martinac, 2005;Dodds & Kuehnel, 2010;Kasim, 2006;Merwe & Wöcke, 2007, among others). Inevitably, there were questions which are still relatively unanswered; whether the tourism sector differs from other industries over CSR and its implementation.…”
Section: The Csr Languagementioning
confidence: 99%
“…If we consider each of the TBL pillars (financial, social, and environmental reporting) separately, there are many claims in the literature that financial, social and environmental reporting can give hotels a sustainable competitive advantage (Kirk, 1995;Bohdanowicz, 2005;Bramwell and Alletorp, 2001;Bohdanowicz et al, 2005;Chan and Wong, 2006;Erdogan and Baris, 2007). Financial reporting, for instance, may lead to improved performance by allowing hotels to attract capitals through being more transparent with investors, and through lowering over-investment, lower under-investment, or both (Biddel et al, 2009).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%